Effects of High Environmental Temperature on Blood Indices of Thai Indigenous Chickens, Thai Indigenous Chickens Crossbred and Broilers - Aengwanich, W. (International Journal of Poultry Science, 2007)
The purpose of this experiment was to determine the effects of high environmental temperature on the blood indices (mean corpuscular volume, MCV; mean corpuscular hemoglobin, MCH; mean corpuscular hemoglobin concentration, MCHC) of Thai Indigenous Chickens (TIC), Thai Indigenous Chickens Crossbred (TICC) and broilers (BC). One kilogram of male and female TIC, TICC and BC were maintained in an environmental temperature range of 26±2°C and 38±2°C. MCV, MCH and MCHC were investigated on days 1, 7, 14, 21 and 28 of an experimental period. The results revealed the following information: On day 14 of the experimental period, MCV of the chickens maintained at 38±2°C was significantly higher than that of chickens maintained at 26±2°C (p<0.05). MCH of the chickens maintained in the environmental temperature at 38±2°C was significantly decreased during days 1-14 and then increased on day 21 of the experimental period (p<0.05). The MCH of chickens maintained at 26±2°C was significantly decreased during days 7-21 and then increased on day 28 of experimental period (p<0.05). On days 1 and 21, the MCH of chickens maintained in the environmental temperature at 38±2°C was significantly higher than that of chickens at 26±2°C (p<0.05). The MCHC of chickens maintained at 38±2°C was significantly higher than that of chickens at 26±2°C (p<0.05). Moreover, the MCHC of the TICC changed less than that of the TIC and BC (p<0.05). This experiment showed that the high environmental temperature had an effects on the chickens blood indices and more specifically, the MCHC of the TIC and BC responsed to high heat greater than TICC.